Self‐Euthanasia, the Dutch Experience: In Search for the Meaning of a Good Death or Eu Thanatos. (9th September 2016) - Vink, Ton
Abstract: My main purpose in this article is to establish the meaning of a 'good death' when death is self‐chosen. I will take as my point of departure the new notion of 'self‐euthanasia' and the corresponding practice that has evolved in the Netherlands in recent years. Both physician‐euthanasia and self‐euthanasia refer to an ideal process of a good death, the first being ultimately the physician's responsibility, while the second is definitely the responsibility of the individual choosing to die. However, if we also accept the existence of a fundamental moral difference between ending another person's life and ending your own life, and if we accept this moral difference to be also relevant to the normatively laden good death, then this difference represents a strong reason for preferring self‐euthanasia to physician‐euthanasia.